2020
DOI: 10.1049/iet-map.2019.0623
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐thin metamaterial perfect absorbers for single‐/dual‐/multi‐band microwave applications

Abstract: In this study, the authors present three different metamaterial absorbers (MMAs) namely, T, split‐I (SI) and split‐Jerusalem cross (SJC) with different dimensions and geometrical configurations. The absorption rates of T‐, SI‐ and SJC‐shaped absorbers are studied at microwave frequencies. T‐shaped absorber demonstrates perfect absorption at 10.19 GHz, making it suitable for single band operation, whereas SI‐shaped absorber exhibits two perfect absorption peaks at 9.32 and 10.75 GHz finding its application in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…17 The polarization-sensitive nature of the structure demonstrates the practical applications in various fields including polarization detection and sensing. 17,18 Further, it is observed that the absorber is insensitive to incident angles till 45 o , and after that, absorption is reduced with increase in the angle, as illustrated in Fig. 4b.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…17 The polarization-sensitive nature of the structure demonstrates the practical applications in various fields including polarization detection and sensing. 17,18 Further, it is observed that the absorber is insensitive to incident angles till 45 o , and after that, absorption is reduced with increase in the angle, as illustrated in Fig. 4b.…”
Section: Resultsmentioning
confidence: 83%
“…As shown in Fig. 3a, the normalized impedance (Z) 9,18 of the proposed absorber is 0.88 + j0.08, 1.07 À j0.18 and 1.04 À j0.03 at 3.36 GHz, 3.95 GHz and 10.48 GHz, respectively. The equivalent circuit for the proposed absorber given in the inset of Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations